Analisis Variabel-Variabel yang Mempengaruhi Kualitas Hasil Pemeriksaan (Studi Pada Insektorat Provinsi Kalimantan Selatan) - Chairina Chairina; Sarwani Sarwani (JURNAL BISNIS DAN PEMBANGUNAN, 2018)
This research aims to analyze the effect of competence, continues education, the complexity of the task,  professional skepticism, Objectivity, independence,  due professional  care and ethics of auditors to quality audit results. The respondents were the 36 in auditors in the Inspectorate of South South Kalimantan Province. The questionnaires distributed 36 exemplars, and returned 36 exemplars or 100 %. The collected data analyzed with multiple linier regression with moderating variable analysis technique use a significance level of 5 % (0,05) through SPSS version 22,0 The result of this research that competence, continues education, the complexity of the task,  professional skepticism, Objectivity, independence influence to quality audit results. While, professional care and ethics of auditors has not influence effect to quality audit results.  Keywords:  quality audit results, competence, continues education, the complexity of the task, professional skepticism, Objectivity, independence, due professional care and ethics of auditors